PENGARUH WOOLWICH MASSAGE MENGGUNAKAN MINYAK ZAITUN DENGAN KEBERHASILAN MENYUSUI PADA IBU NIFAS POST SC DI RSU SEBENING KASIH TAYU - Ummi Sa’adah; Ana Zumrotun Nisak; Dwi Astuti (Jurnal Medicare, 2026)
Breastfeeding is the process of feeding breast milk to babies from birth to 2 years of age with the aim of providing optimal nutrition to babies. This study aims to analyse the effect of Woolwich massage using olive oil on breastfeeding success in post-caesarean section mothers at Sebening Kasih General Hospital. The research method used was quantitative, namely a quasi-experimental study with a two-group pretest-posttest design. The population consisted of 142 post-caesarean section mothers. The sample size was calculated using the Slovin formula to be 60, with a ratio of 30 respondents receiving the intervention and 30 respondents in the control group. The analysis in this study used the Wilcoxon Sign Rank test. The results of the study showed that before and after the intervention of Woolwich massage using olive oil, there was a significant increase in the success rate of breastfeeding, especially among postpartum mothers who had undergone a caesarean section and received Woolwich massage using olive oil.